GerpavGrid: using the Grid to maintain the city road system - De Rose, Cesar A. F.; Ferreto, Tiago C.; Farias, Marcelo B. De; Dias, Vladimir G.; Cirne, Walfredo; Oliveira, Milena P. M.; Saikoski, Katia; Danieleski, Maria Luiza (Anais do International Symposium on Computer Architecture and High Performance Computing (SBAC-PAD), 2006)
This paper presents and evaluates a governmental application that has been ported to run in a Grid. The Gerpav application is used in the city of Porto Alegre, located in the south of Brazil, to maintain and plan the investments in the city road system, and Grid technology brought substantial performance gains to its distributed version called GerpavGrid. We describe several optimizations strategies used in GerpavGrid to move the bottleneck of the sequential application from database to memory to facilitate distribution of tasks in the Grid. Results of its execution in a real Grid are also presented, and show that a Grid can be also an interesting execution platform for non-classical HPC applications that are database intensive.